Investigation of the Fatigue Performance of Sustainable Asphalt Pavement - Elkut, Foad; Hamzah, Meor (Journal of Pure & Applied Sciences, 2023)
Selecting suitable materials for sustainable asphalt pavement construction can be a challenging task, particularly due to the significant issue of fatigue damage in flexible pavement. The fatigue performance of gap-graded asphalt mixes (GGCP) was assessed through four-point bending beam fatigue testing, examining the impact of incorporating 6% Calcium carbonate (CaCO3) and 2% treated palm oil fuel ash (TPOFA) on fatigue cracking. The testing was conducted at various stress levels (800, 1000, and 1200 kPa) and a temperature of 5°C. Additionally, the asphalt mixtures underwent acceleration ageing and moisture conditions, which varied during the study. The experimental findings indicated that higher stress levels resulted in a decrease in the fatigue life of asphalt mixtures due to ageing effects. Moreover, moisture conditioning was found to diminish the fatigue life of the asphalt mixture. Comparatively, the fatigue model incorporating a plateau value and fatigue life demonstrated greater accuracy when compared to previous regression models.